Pembelajaran Daring dan Luring pada Masa Pandemi Covid-19 - Pratama, Rio Erwan; Mulyati, Sri; Susanto, Iwan (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to explore whether online learning and offline learning can work well, so that educational goals can be achieved. This research is a phenomenological qualitative research to find out how the application of online learning and offline learning in one of the SD Negeri Sepatnunggal 02 in Cilacap Regency, Central Java, Indonesia. The steps of this research include action planning, action implementation, observation stage, and reflection stage. From the results of the study, there were several obstacles in its implementation, but they could be solved well by the teacher in order to educate the students. Both online and offline learning systems are expected for teachers to be creative in educating students, so that learning success can be achieved properly or effectively. This study provides information that teachers actually prefer offline learning where they can interact with students, and also students prefer offline learning with face-to-face interactions.